Evaluación de diferentes dosis de microorganismos de montaña sobre el crecimiento y desarrollo de las plántulas de lechuga (Lactuca sativa), en la zona de Montalvo - LOPEZ ARELLANO, OSCAR ADRIAN (2023)
The objective of this research was to evaluate the different doses of mountain microorganisms on the growth and development of lettuce (Lactuca sativa L.) seedlings in the Montalvo area. The research work was carried out in Las Mercedes de Aguas Blancas, Canton Montalvo, Province of Los Ríos. A randomized block design with five treatments and four replications was applied. Comparisons of means were made using Tukey's test at 5% statistical significance. The variables evaluated were: plant height, number of leaves per plant, leaf length and width, leaf width and fresh weight of lettuce leaf area. Through the results obtained, it was determined that the applications of mountain microorganisms, showed a significant incidence on the agronomic variables evaluated in lettuce seedlings; the agronomic variables plant height, number of leaves per plant and length and width of leaves, presented high statistical significance over the applied control; the best results were achieved with the application of mountain microorganisms in doses of 100 cc⁄5 L H2O in the agronomic variables: plant height, number of leaves per plant and leaf length and width; the variables fresh weight and dry matter aerial part, presented high statistical significance over the applied control and the best averages of fresh weight and dry matter aerial part of lettuce seedlings were achieved with the use of mountain microorganisms in doses of 100 cc⁄5 L H2O.